INTRODUCTION TO DOUGLAS J. OSLER’S "IMAGES OF LEGAL HUMANISM" - Pfeiffer, K. (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 2001)
In the context of the Third International Conference on Humanistic Discourse, this text introduces Douglas J. Osler’s "Images of Legal Humanism".